2006
DOI: 10.2174/138955706776073501
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease in Diabetes

Abstract: Diabetes is associated with a marked increase in the risk of atherosclerotic vascular disorders, including coronary, cerebrovascular, and peripheral artery disease. Cardiovascular disease (CVD) could account for disabilities and high mortality rates in patients with diabetes. In this paper, we review the molecular mechanisms for accelerated atherosclerosis in diabetes, especially focusing on postprandial hyperglycemia, advanced glycation end products (AGEs) and the renin-angiotensin system. We also discuss her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 80 publications
0
13
0
1
Order By: Relevance
“…10,11 Recent understanding of this process has confirmed that the interaction between AGEs and their receptor (RAGE) generates oxidative stress and plays a role in altered gene expression of growth factors and cytokines, and is thus involved in the pathogenesis of diabetic nephropathy. 12,13 In fact, there is compelling evidence that the formation and accumulation of AGEs mediates the progressive alteration of renal architecture and loss of renal function in diabetic nephropathy. 14 -16 Since the pathophysiological crosstalk between the AGEs-RAGE system and angiotensin II (Ang II) also plays a role in diabetic nephropathy, 17 -19 we examined here whether telmisartan, a unique Ang II type 1 receptor blocker with peroxisome proliferator-activated receptor-γ (PPAR-γ)-modulating activity, could inhibit MCP-1 expression in AGEs-exposed human mesangial cells.…”
Section: -9mentioning
confidence: 99%
“…10,11 Recent understanding of this process has confirmed that the interaction between AGEs and their receptor (RAGE) generates oxidative stress and plays a role in altered gene expression of growth factors and cytokines, and is thus involved in the pathogenesis of diabetic nephropathy. 12,13 In fact, there is compelling evidence that the formation and accumulation of AGEs mediates the progressive alteration of renal architecture and loss of renal function in diabetic nephropathy. 14 -16 Since the pathophysiological crosstalk between the AGEs-RAGE system and angiotensin II (Ang II) also plays a role in diabetic nephropathy, 17 -19 we examined here whether telmisartan, a unique Ang II type 1 receptor blocker with peroxisome proliferator-activated receptor-γ (PPAR-γ)-modulating activity, could inhibit MCP-1 expression in AGEs-exposed human mesangial cells.…”
Section: -9mentioning
confidence: 99%
“…It is estimated that the number of people diagnosed with diabetes is expected to grow from 171 million in 2000 to 366-440 million by 2030, with three-quarters of the patients living in lowincome countries (1). Besides being associated with major complications, such as cardiovascular disease, atherosclerosis, retinopathy, nephropathy, and neuropathy (2)(3)(4)(5), prevalence of infections is also much more common in diabetic individuals. This increased susceptibility to infection has been attributed to neutrophil dysfunction, dehydration, malnutrition, vascular insufficiency, and neuropathy (6).…”
Section: Introductionmentioning
confidence: 99%
“…The same regulatory control severely confines PDC activity in diabetic animals, obstructing consumption of abundant glucose [6-9, 86-88, 93, 96]. This contributes to elevated blood glucose and protein glycation, which causes damage to the vascular system [141][142][143][144]. Glucose oxidation is also decreased in obese individuals (including man); in studies with obese rats and mice, this is linked to a low percentage of the PDC being in the active form, at least in part due to insulin resistance [1,3,4,6,32].…”
mentioning
confidence: 99%